Computer Programming for Librarians: A Study of Job Postings for Library Technologists. - Gonzales, Brighid M. (Journal of Web Librarianship)
The rapid changes in technology used in the library and cultural heritage sectors can make it difficult for early career librarians and LIS students interested in library technology positions to know what skills will be most beneficial to their job search. In this study, 492 librarian and archivist job postings from the Code4Libs Jobs website from between 2008 and 2018 were collected and analyzed to find which programming technologies are most in demand overall and which are most requested for specific types of jobs and specific types of employers, including changes over time. The results provide a glimpse of programming languages and technologies that are widely useful in the field of library technology today, as well as those that are growing in use.